MRI of the Elbow: How to Do It - Pazahr, Shila; Sutter, Reto; Zubler, Veronika (Seminars in Musculoskeletal Radiology, 2021)
The diagnostic cascade for elbow complaints starts with the physical examination and radiographs that already can clarify or rule out many causes. Depending on the suspected pathology, additional imaging is necessary. Magnetic resonance imaging (MRI) has the advantage of accurately demonstrating a broad spectrum of diseases. The main indication for noncontrast MRI of the elbow is chronic epicondylitis. For magnetic resonance (MR) arthrography, it is suspected chondral and osteochondral abnormalities. Indirect MR arthrography is an option when direct arthrography is not practicable. MR arthrography of the elbow with traction is feasible, with promising results for the assessment of the radiocapitellar cartilage.
Keywords: elbow magnetic resonance imaging; elbow arthrography; elbow imaging